K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

7 tháng 10 2017

a/ x2 + 3x - 18 = 0

x2 -3x + 6x - 18 = 0

x(x-3) + 6(x-3) = 0

(x-3)(x+6) = 0

Suy ra: x - 3 = 0 hoặc x + 6 = 0

hay x = 3 hoặc x = - 6

Vậy x thuộc {3;-6}.

b/ 8x2 + 30x + 7 = 0

8x2 + 2x + 28x + 7 = 0

2x(4x+1) + 7(4x+1) = 0

(4x+1)(2x+7) = 0

Suy ra: 4x + 1 = 0 hoặc 2x + 7 = 0

hay x = -1/4 hoặc x = -7/2

Vậy x thuộc {-1/4; -7/2}.

c/ x3 - 11x2 + 30x = 0

x(x2 - 11x + 30) = 0

x(x2 - 5x - 6x + 30) = 0

x.[x(x-5) - 6(x-5)] = 0

x(x-5)(x-6) = 0

Suy ra: x = 0; x - 5 = 0 hoặc x - 6 = 0

hay x = 0; x =5; x =6

Vậy x thuộc {0;5;6}.

11 tháng 8 2016

a) \(8x^2+30x+7=0\)

\(\Leftrightarrow8\left(x^2+\frac{15}{4}x+7\right)=0\)

\(\Leftrightarrow x^2+\frac{1}{4}x+\frac{7}{2}x+\frac{7}{8}=0\) 

\(\Leftrightarrow x\left(x+\frac{1}{4}\right)+\frac{7}{2}\left(x+\frac{1}{4}\right)=0\)

\(\Leftrightarrow\left(x+\frac{1}{4}\right)\left(x+\frac{7}{2}\right)=0\)

\(\Leftrightarrow\left[\begin{array}{nghiempt}x+\frac{1}{4}=0\\x+\frac{7}{2}=0\end{array}\right.\)\(\Leftrightarrow\left[\begin{array}{nghiempt}x=-\frac{1}{4}\\x=-\frac{7}{2}\end{array}\right.\)

 

11 tháng 8 2016

b)\(x^3-11x^2+30x=0\)

\(\Leftrightarrow x\left(x^2-11x+30\right)=0\)

\(\Leftrightarrow x\left(x^2-5x-6x+30\right)=0\)

\(\Leftrightarrow x\left[x\left(x-5\right)-6\left(x-5\right)\right]=0\)

\(\Leftrightarrow x\left(x-5\right)\left(x-6\right)=0\)

\(\Leftrightarrow\left[\begin{array}{nghiempt}x=0\\x-5=0\\x-6=0\end{array}\right.\)\(\Leftrightarrow\left[\begin{array}{nghiempt}x=0\\x=5\\x=6\end{array}\right.\)

10 tháng 8 2017

a) \(8x^2+30x+7=0\)
\(\Rightarrow8x^2+2x+28x+7=0\)
\(\Rightarrow2x\left(4x+1\right)+7\left(4x+1\right)=0\)
\(\Rightarrow\left(2x+7\right)\left(4x+1\right)=0\)
\(\Rightarrow\)\(2x+7=0\)  hoặc  \(4x+1=0\)
\(\Rightarrow\)\(2x=-7\)          ;     \(4x=-1\)
\(\Rightarrow\)\(x=\frac{-7}{2}\)             ;     \(x=\frac{-1}{4}\)
Vậy \(x\in\left\{\frac{-7}{2};\frac{-1}{4}\right\}\)

b) \(x^3-11x^2+30x=0\)
\(\Rightarrow x\left(x^2-11x+30\right)=0\)
\(\Rightarrow x\left(x^2-6x-5x+30\right)=0\)
\(\Rightarrow x\left[x\left(x-6\right)-5\left(x-6\right)\right]=0\)
\(\Rightarrow x\left(x-5\right)\left(x-6\right)=0\)
\(\Rightarrow\)\(x=0\)  hoặc  \(x-5=0\)  hoặc  \(x-6=0\)
\(\Rightarrow\)\(x=0\)     ;      \(x=5\)               ;     \(x=6\)
Vậy \(x\in\left\{0;5;6\right\}\)

10 tháng 8 2017

a)\(8x^2+30x+7=0\Leftrightarrow8x^2+2x+28x+7=0\Leftrightarrow2x\left(4x+1\right)+7\left(4x+1\right)=0\)

\(\Leftrightarrow\left(2x+7\right)\left(4x+1\right)=0\Leftrightarrow\orbr{\begin{cases}2x+7=0\\4x+1=0\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=-\frac{7}{2}\\x=-\frac{1}{4}\end{cases}}\)

b)\(x^3-11x^2+30x=0\Leftrightarrow x\left(x^2-11x+30\right)=0\Leftrightarrow x\left(x^2-5x-6x+30\right)=0\)

\(\Leftrightarrow x\left[x\left(x-5\right)-6\left(x-5\right)\right]=0\Leftrightarrow x\left(x-6\right)\left(x-5\right)=0\)

<=>x=0 hoặc x-6=0 hoặc x-5=0 <=> x=0 hoặc x=6 hoặc x=5

21 tháng 10 2016

8x2+30x+7=0

 8x2+16x+14x+7=0

8x(x+2) +7(x+2)=0

(8x+7)(x+2)=0

=>\(\orbr{\begin{cases}8x+7=0\\x+2=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-\frac{7}{8}\\x=-2\end{cases}}}\)

21 tháng 10 2016

a)

4x2-8x+4=2(1-x)(x+1)

4x2-8x+4-2+2x2=0

6x2-8x+2=0

2(3x2-4x+1)=0

3x2-3x-x+1=0

3x(x-1) -(x-1)=0

(3x-1)(x-1)=0

\(\Rightarrow\orbr{\begin{cases}3x-1=0\\x-1=0\end{cases}\Rightarrow\orbr{\begin{cases}x=\frac{1}{3}\\x=1\end{cases}}}\)

29 tháng 8 2017

Bài 1

A,7x − 6x 2 − 2 = −(6x 2 − 7x + 2)

= −(6x 2 − 3x − 4x + 2)

= −[3x(2x − 1) − 2(2x − 1)] = −(3x − 2)(2x −1)

b,\(2x^2+3x-5\)

=\(2x^2-2x+5x-5\)=\(2x\left(x-1\right)+5\left(x-1\right)=\left(2x+5\right)\left(x-1\right)\)

5 tháng 9 2019

\(x^2+7x+12=x^2+3x+4x+12=x\left(x+3\right)+4\left(x+3\right)=\left(x+3\right)\left(x+4\right)=0\)

\(x^2+3x-18=0\Leftrightarrow x^2-3x+6x-18=x\left(x-3\right)+6\left(x-3\right)=\left(x+6\right)\left(x-3\right)=0\)

5 tháng 9 2019

b) \(x^2-10x+16\)

\(=x^2-2x-8x+16\)

\(=x\left(x-2\right)-8\left(x-2\right)\)

\(=\left(x-2\right)\left(x-8\right)\)

c) \(x^2+6x+8\)

\(=x^2+2x+4x+8\)

\(=x\left(x+2\right)+4\left(x+2\right)\)

\(=\left(x+2\right)\left(x+4\right)\)

d) tươn tự c

e) \(x^2+3x-18=0\)

\(\Leftrightarrow x^2+6x-3x-18=0\)

\(\Leftrightarrow x\left(x+6\right)-3\left(x+6\right)=0\)

\(\Leftrightarrow\left(x+6\right)\left(x-3\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x+6=0\\x-3=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-6\\x=3\end{cases}}}\)

Vậy ,...

18 tháng 3 2020

rrrrrrrr\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)

6 tháng 10 2019

a) \(8x^3-x=0\)

\(\Leftrightarrow x\left(8x^2-1\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x=0\\8x^2-1=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\pm\sqrt{\frac{1}{8}}\end{cases}}\)

b) \(x\left(x-5\right)=2x-10\)

\(\Leftrightarrow x\left(x-5\right)=2\left(x-5\right)\)

\(\Leftrightarrow x\left(x-5\right)-2\left(x-5\right)=0\)

\(\Leftrightarrow\left(x-2\right)\left(x-5\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x-2=0\\x-5=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=2\\x=5\end{cases}}\)

6 tháng 10 2019

c) \(3x^2+30x=-75\)

\(\Leftrightarrow x^2+10x=-25\)

\(\Leftrightarrow x^2+10x+25=0\)

\(\Leftrightarrow\left(x+5\right)^2=0\)

\(\Leftrightarrow x+5=0\Leftrightarrow x=-5\)

17 tháng 8 2016

1)x2-8x-9

= x^2 - 9x +x -9

= x(x+1) - 9 (x+1)

= (x-9) (x+1)

2)x2+3x-18

3)x3-5x2+4x

=x^3 - 4x^2 - x^2 + 4x 

= x^2 (x-1) - 4x(x-1)

= (x^2 - 4x) (x-1)

= x(x-4)(x-1)

4)x3-11x2+30x

5)x3-7x-6

6)x16-64

\(=\left(x^8\right)^2-8^2\)

\(=\left(x^8-8\right)\left(x^8+8\right)\)

7)x3-5x2+8x-4

8)x2-3x+2

= x^2 - 2x - x +2

= x(x-1) -2(x-1)

= (x-2)(x-1)

17 tháng 8 2016

1)   \(\left(x-9\right)\left(x+1\right)\)             2)   \(\left(x-3\right)\left(x+6\right)\)                                           3)   \(x\left(x-4\right)\left(x-1\right)\)

4)    \(x\left(x-6\right)\left(x-5\right)\)         5)\(\left(x-3\right)\left(x+1\right)\left(x+2\right)\)                               6)   ........

7)  \(\left(x-1\right)\left(x-2\right)\left(x-2\right)\)          8)   \(\left(x-2\right)\left(x-1\right)\)